2016
DOI: 10.1002/cite.201600014
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic Zero Discharge Fluid Dynamic Gauging for Measuring the Thickness of Soft Layers on Surfaces

Abstract: A bench-top device that can be used to perform fluid dynamic gauging measurements of soft solid layers with zero net liquid discharge and potentially under aseptic (closed system) conditions is demonstrated. Testing results are presented for Newtonian liquids with a range of viscosities: deionised water, 8 wt% and 10 wt% sucrose solutions, 18 wt% glycerol/water solutions and a paraffin oil (1.12-1000 mPa s). The experimental data for discharge coefficient, C d , against clearance/nozzle throat diameter, h/d t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 9 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…The effect of cracking is discussed briefly. FDG measurements assume a smooth interface whereas the CMS layer is rough and features cracks of depth δ o : Wang et al 3 investigated the impact of surface roughness experimentally and showed that surface roughness leads to C d being overestimated so that δ is therefore underestimated. The cracks in the CMS layers, moreover, present flow channels and allow more liquid to pass than a uniform surface would (or give a lower pressure drop for a given flow rate).…”
Section: Swelling Of Soft Solid Layersmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of cracking is discussed briefly. FDG measurements assume a smooth interface whereas the CMS layer is rough and features cracks of depth δ o : Wang et al 3 investigated the impact of surface roughness experimentally and showed that surface roughness leads to C d being overestimated so that δ is therefore underestimated. The cracks in the CMS layers, moreover, present flow channels and allow more liquid to pass than a uniform surface would (or give a lower pressure drop for a given flow rate).…”
Section: Swelling Of Soft Solid Layersmentioning
confidence: 99%
“…where δ ∞ is the equilibrium thickness, 3 chains. 28 At high pH, PVAc undergoes hydrolysis to give poly(vinyl alcohol; PVA) and acetic acid.…”
Section: Effect Of Phmentioning
confidence: 99%
See 2 more Smart Citations
“…By using syringe pumps to introduce or withdraw fluid at a fixed or adjustable rate in an alternating sequence, the total volume of solution does not change, thereby achieving zero net flow (giving ZFDG, see Yang et al, 2014). This enables aseptic operation, as well as supporting testing with solutions of high value or significant safety risk (Wang et al, 2016). The photograph in Figure 1(b) shows the ZFDG unit used in the work on biofilms reported here.…”
Section: Introductionmentioning
confidence: 99%